2018
DOI: 10.3390/nu10010069
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, Inflammation, Atherosclerosis Syndrome (MIA) and Diet Recommendations among End-Stage Renal Disease Patients Treated with Maintenance Hemodialysis

Abstract: Malnutrition-inflammation-atherosclerosis syndrome is one of the causes of increased mortality in chronic kidney disease (CKD). The aim of the study was to assess the inflammation and nutritional status of patients in end-stage kidney disease treated with maintenance hemodialysis. The study included a group of 98 hemodialyzed patients with stage 5 CKD (38 women and 60 men). Albumin, prealbumin (PRE), and C-reactive protein (CRP) were measured in serum samples collected before mid-week dialysis. Fruit and veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 31 publications
4
66
0
2
Order By: Relevance
“…The finding that TGF- β 1 levels demonstrated a modest significant correlation with hs-CRP and albumin (a marker of malnutrition) was consistent with the report of Stefoni et al [ 40 ]. Furthermore, previous studies had suggested a link between malnutrition, inflammation, and cardiovascular disease morbidity and mortality in end-stage renal disease patients [ 51 54 ]. Therefore, the association between serum TGF- β 1 levels and hs-CRP may suggest the degree of vascular inflammation, while correlation with low serum albumin may suggest a state of malnutrition which is very common in CKD patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that TGF- β 1 levels demonstrated a modest significant correlation with hs-CRP and albumin (a marker of malnutrition) was consistent with the report of Stefoni et al [ 40 ]. Furthermore, previous studies had suggested a link between malnutrition, inflammation, and cardiovascular disease morbidity and mortality in end-stage renal disease patients [ 51 54 ]. Therefore, the association between serum TGF- β 1 levels and hs-CRP may suggest the degree of vascular inflammation, while correlation with low serum albumin may suggest a state of malnutrition which is very common in CKD patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…are associated with frailty and anaemia, respectively, and markers of inflammation which are involved in the malnutrition-inflammation-atherosclerosis (MIA) syndrome [48][49][50]. Serum protein levels are prognostic factors related to frailty in patients with ESKD [50].…”
Section: Plos Onementioning
confidence: 99%
“…Systemic chronic inflammation is a frequent and unsolved problem of patients with CKD . This chronic inflammatory process causes malnutrition, inflammation, and atherosclerosis (MIA) syndrome which is associated with increased mortality and decreased quality of life .…”
Section: Discussionmentioning
confidence: 99%